EFL Students’ Experiences with the Role of Lyrics in Song-Based Listening Activities - Chofifah, Ummi; Zainuddin, Zainuddin; Hariati, Nina Agus (Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
The purpose of this study is to explore how EFL students perceive the role of lyrics in song-based listening activities. Students’ perceptions of the use of lyrics during listening practice were investigated using a qualitative descriptive research approach. Five university students who had experience listening to English songs with lyrics were intentionally selected as participants. This study concentrated on their authentic listening practices rather than using an intervention-based design. Semi-structured interviews, documentation, and observation were used to gather data. Miles and Huberman’s interactive qualitative analysis model, which incorporates data reduction, data display, and conclusion drafting, was used to examine the data. The results show that during listening exercises, participants described lyrics as visual aids that helped them follow spoken input, identify words, and comprehend song meaning. Additionally, participants reported that listening was more comfortable and engaging when lyrics were present. However, some participants reported difficulty comprehending both audio and lyrics simultaneously, particularly in songs with fast-paced sections or unfamiliar terminology. Overall, students view lyrics as a supportive component of their listening experiences. This study is limited by the small sample size, which may limit the generalizability of the findings. Despite this limitation, the results indicate that incorporating lyrics into song-based listening activities can support students’ comprehension and motivation, particularly in informal learning contexts. Future research is therefore recommended to include larger samples and examine additional variables, such as proficiency levels and song genres, to gain a deeper understanding of the role of lyrics in EFL listening development.